2016
DOI: 10.1007/s10493-016-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimated crop loss due to coconut mite and financial analysis of controlling the pest using the acaricide abamectin

Abstract: Reducing the losses caused by Aceria guerreronis Keifer has been an arduous task for farmers. However, there are no detailed studies on losses that simultaneously analyse correlated parameters, and very few studies that address the economic viability of chemical control, the main strategy for managing this pest. In this study the objectives were (1) to estimate the crop loss due to coconut mite and (2) to perform a financial analysis of acaricide application to control the pest. For this, the following paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Avermectin, a biological insecticide, is a macrocyclic lactone compound with strong activity against a broad spectrum of pests combined with low toxicity to non-target organisms [ 4 – 6 ]. However, the low water solubility and instability to light seriously influence its bioavailability and shelf life [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Avermectin, a biological insecticide, is a macrocyclic lactone compound with strong activity against a broad spectrum of pests combined with low toxicity to non-target organisms [ 4 – 6 ]. However, the low water solubility and instability to light seriously influence its bioavailability and shelf life [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, it has been reported that Ac. guererronis infestations cause significant premature coconut drop (Nair, 2002; Rezende et al ., 2016). If Ac.…”
Section: Discussionmentioning
confidence: 99%
“…The coconut palm is a perennial plant native to Southeast Asia but is currently distributed throughout the pantropics (Chan and Elevitch, 2006;Gunn et al, 2011;Ahuja et al, 2014) and considered a crop of economic importance in many countries (Hoe, 2018). Mites and months are considered important coconut pests around the world, usually related to decreasing production of coconut fruits due to damage and abortion of the reproductive structure (Bondar, 1940;Moore, 2001;Fernando and Aratchige, 2010;Navia et al, 2013;Rezende et al, 2016). Larvae of different species of moths feed on the male and female flowers of coconuts (Bondar, 1940;Moore, 2001;Cock and Burris, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Crop productivity and the price of agricultural products have not been optimally determined given the influence of these components of IPM programs on EILs and sequential sampling plans. In today's competitive world, we must maximize the use of financial resources, reduce losses caused by pests, and preserve the environment . Therefore, the effects of crop productivity and the price of agricultural products should be considered in determining pest control decision‐making systems.…”
Section: Discussionmentioning
confidence: 99%
“…In today's competitive world, we must maximize the use of financial resources, reduce losses caused by pests, and preserve the environment. [35][36][37] Therefore, the effects of crop productivity and the price of agricultural products should be considered in determining pest control decision-making systems. In this context, this study represents a step towards this reality.…”
Section: Discussionmentioning
confidence: 99%